MUST handbook 2001. (Styles and Classics Philippines, 1998)
Offers up-to-date practical information for motorists and travelers in Manila such as emergency hotlines, utility locations, latest road rules, and vehicle maintenance. It also contains Street Maps of Metro Manila and "Easy Maps" for frequently traveled destinations in the country. This edition features additional guides on keeping healthy while vacationing.